2021
DOI: 10.5603/gp.a2021.0088
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and its receptor in selected obstetrical complications

Abstract: Vitamin D3 (VD3) and its steroidal nuclear receptor are necessary for proper development of a pregnancy. They play a key role in implantation, modulate the mother's immune response to the developing fetus, influence the final development of a placenta, and regulate blood pressure and glucose tolerance. VD3 deficiency can lead to the occurrence of obstetric complications such as recurrent miscarriages, preeclampsia, intrauterine growth restriction, gestational diabetes and preterm labor. VD3 deficiency is a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(Roth 2011) Magielda-Stola et al stated that vitamin D supplementation is a safe treatment option with no risk of side effects or toxicity. Vitamin D supplementation should be given at the planning stage of pregnancy in order to get the most beneficial effect, with serum vitamin D levels in excess of 30 ng/mL [127].…”
Section: Safety Of Vitamin D Supplements Prescription During Pregnancymentioning
confidence: 99%
“…(Roth 2011) Magielda-Stola et al stated that vitamin D supplementation is a safe treatment option with no risk of side effects or toxicity. Vitamin D supplementation should be given at the planning stage of pregnancy in order to get the most beneficial effect, with serum vitamin D levels in excess of 30 ng/mL [127].…”
Section: Safety Of Vitamin D Supplements Prescription During Pregnancymentioning
confidence: 99%
“…Magielda-Stola et al stated that vitamin D3 supplementation is a safe treatment option with no risk of side effects or toxicity. Vitamin D3 supplementation should be given at the planning stage of pregnancy in order to receive the most beneficial effect, with serum 25(OH)D levels in excess of 30 ng/mL [ 128 ].…”
Section: Safety Of Vitamin D3 Supplements Prescription During Pregnancymentioning
confidence: 99%
“…It was demonstrated conclusively that the proper VD level during pregnancy and appropriate placental expression of genes linked to the VD pathway are crucial for the growth and function of the placenta [21]. On the other hand, several studies have shown that vitamin D deficiency could be strongly associated with preeclampsia development [22][23][24][25]. This fact may be related to changes in VDR and hydrolase placental expression, which disturb VD metabolism in preeclamptic women.…”
Section: Introductionmentioning
confidence: 99%